Development and validation of college students' tuberculosis knowledge, attitudes and practices questionnaire (CS-TBKAPQ) - Hualin Jiang; Shaoru Zhang; Yi Ding; Yuelu Li; Tianhua Zhang; Weiping Liu; Yahui Fan; Yan Li; Rongqiang Zhang; Xuexue Ma (BMC, 2017)
Abstract Background China faces many challenges in controlling tuberculosis (TB). One significant challenge is the control of college students' TB. In particular, cross-sectional studies of college students' knowledge, attitudes and practices (KAP) in regard to TB have attracted substantial attention. However, few measurement tools have been developed to aid processes related to expert consultation, pre-testing, reliability and validity testing. Our study developed the College Students' TB Knowledge Attitudes and Practices Questionnaire (CS-TBKAPQ) following the scale development steps. Methods The construction of the CS-TBKAPQ was based on the Theory of Knowledge, Attitude, Belief, and Practice (KABP or KAP). The item pool was compiled from literature reviews and individual interviews. The reliability validation was assessed by calculating Cronbach's α coefficient, the split-half reliability coefficient, and the test-retest reliability coefficient. Construct validity was assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The diagnostic accuracy was evaluated using the World Health Organization Advocacy, Communication and Social Mobilization KAP Survey Questionnaire (WHO-TBKAPQ) as the reference standard. Results A total of 31 questionnaire items were proposed. Cronbach's α coefficient, the split-half reliability coefficient and the test-retest reliability coefficient were 0.86, 0.78 and 0.91. Four factors that explained 62.52% of the total variance were also identified in EFA and confirmed in CFA. The CFA model fit indices were x 2 /df = 1.82 (p < 0.001), GFI = 0.925, AGFI = 0.900, RMR = 0.068, and RMSEA = 0.049. The CS-TBKAPQ was significantly correlated with the WHO-TBKAPQ and the Chinese Public TB KAP Questionnaire (CDC-TBKAPQ) developed by the Chinese Center for Disease Control and Prevention (r = 0.59, 0.60, p < 0.001). The receiver operating characteristics curve (ROC) analysis suggested a cut-off point of 47.5, with which the CS-TBKAPQ showed a sensitivity of 73.63% and a specificity of 80.51% in identifying students with low-level KAP. The positive and negative predictive values were 83.23% and 69.91%. Conclusions The findings of this study demonstrate that the CS-TBKAPQ is a reliable and valid tool for measuring the KAP towards TB in college students.